Pre-Linguistic Development Among Children in Indonesia: A Psycholinguistic Perspective - Supriyadi, Moh.; Muhammad, Jiddah Hassan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The pre-linguistic stage represents a crucial foundation in children’s language development, characterized by non-verbal communication such as crying, cooing, and babbling. This study addresses the problem of understanding how early non-verbal behaviors form the basis for later linguistic competence, particularly within the Indonesian context, where linguistic diversity adds complexity to language acquisition. The objective of this research is to describe the stages of pre-linguistic development in children of varying ages and to analyze the factors influencing their progress. Employing a descriptive qualitative approach, data were collected through observation and interviews with parents and caregivers, followed by content analysis to identify recurring behavioral patterns. The analysis considered the frequency of communicative behaviors, the contexts in which they occurred, and the role of adult responses in shaping children’s early language skills. The findings reveal that language development among Indonesian children is influenced by overlapping factors including family environment, multilingual exposure, educational practices, and digital technology. Children raised in linguistically supportive environments exhibit faster and more effective language growth, especially in their early years. This study contributes to the understanding of early language development by highlighting both the opportunities and challenges of multilingual contexts, offering insights for educators, parents, and policymakers in fostering optimal language acquisition